The Effect of Peritoneal Fluid from Patients with Endometriosis on Mitochondrial Function and Development of Early Mouse Embryos - Shu, Jing; Xing, Lili; Ding, Guolian; Luo, Qiong; Liu, Xinmei; Yan, Qingfeng; Sheng, Jianzhong; Huang, Hefeng (PloS one, 2013)
Peritoneal fluid (PF) from patients with endometriosis can inhibit early embryo development via probable functional changes of embryo mitochondria in the early stage of embryo development. The purpose of this study was to determine the effect of PF from patients with endometriosis on mitochondrial function and development of early mouse embryos. PF was collected from patients with infertility and endometriosis, infertility due to tubal factors, and normal control subjects, and the level of NO was measured. Early murine embryos were then cultured with PF from normal control subjects, those with endometriosis, and with human tubal fluid (HTF), respectively. Cleavage and blastulation rates, mitochondrial DNA (mtDNA) copy numbers, adenosine triphosphate (ATP) level, and mitochondrial membrane potential (ΔΨm) of the different groups were compared. The NO level in the PF of patients with endometriosis was significantly greater than in those without endometriosis and control patients. The embryos cultures with PF from patients with endometriosis had a lower cleavage rate and blastulation rate, and higher ATP and ΔΨm level at the 2- and 4-cell stages. No significant difference was found in mtDNA copies among the 3 groups. PF from patients with endometriosis can inhibit early embryo development via probable functional changes of embryo mitochondria in the early stage of embryo development. Understanding the effects of PF on embryo development may assist in developing new methods of treatment for infertility.